EVALUASIKEBIJAKAN PEMBUANGAN LIMBAH HASIL PENGERUKAN PENDALAMAN ALUR DAN KOLAM DI PERAIRAN GRESIK KE LOKASI DUMPING DI SELAT MADURA (Studi Kasus Pemberian izin Kepada PT. Indonesia Marina Shipyard untuk melakukan pengerukan pendalaman alur dan kolam guna - Sapto J.Poerwowidagdo; Supriyanto; Nuhman (Faculty of Social and Political Science, 2013)
Policy on dredging permit granted by the Minister of Transport to PT. Indonesia Marina Shipyard (PT IMS) based on the Decree of the Minister of Communications No. B.XXXIV-260 >' PIJ.62, which in legal by the Director General of Sea Transportation on Nth April 2010 concerning the authorization of PT Indonesia Marina Shipyard to conduct dredging deepening groove and ponds for operations TUKS shipyard PT. IMS in the territorial waters of the port ofGresik in East Java Province. This study aimed to evaluate the extent of the implementation of the policy, especially in relation to issues Dredging and dumping activities in the area that has been determined on the recommendation of Adpel Gresik to dumping areas in APBS and recommendations of Adpel Tg. Perak for dumping area at APTS. The method used in this research is a method of qualitative analysis. The results of this study indicate that the Minister of Communications Decree No. B.XXXIV-260 / PU.62 flawed because it does not comply with Regulation No. 21 of 2010 and the implementation of its activities partly obligations are not met by PT. IMS. The importance of close monitoring of the implementation of the program of the agency appointed for the purpose of policy decisions can be realized in line with expectations. Therefore, for the implementation of the decision of the Minister of Transportation's new No. KP 687 in 2012 should be fully implemented in accordance with the Standard Operating Procedure (SOP) of each agency designated to watch.